2022
DOI: 10.1186/s12875-022-01723-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of primary care in informing and supporting people with limited health literacy in the Netherlands during the COVID-19 pandemic: a qualitative interview study

Abstract: Background During the coronavirus disease 2019 (COVID-19) pandemic, people have been confronted with a large amount of information about the virus and the governmental measures against its spreading. However, more than a quarter of individuals have limited health literacy (HL), meaning that they have difficulty finding, understanding, and applying health information. The purpose of this interview study was to investigate how individuals with limited HL acquire information about COVID-19 and gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, this study shows that consideration of the specific needs of people with limited health literacy was delayed and limited to a basic definition, rather than explicitly and consistently taken into account from the start. Knottnerus, Heijmans and Rademakers [34] showed that this was not unique to the rheumatology context, but extends across people with chronic diseases in the Netherlands. While the intersection between crisis communication and health literacy should be further explored, investing in training and guidelines for health literate communication for organisations and health professionals will potentially be useful in general patient communication as well as in times of crisis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this study shows that consideration of the specific needs of people with limited health literacy was delayed and limited to a basic definition, rather than explicitly and consistently taken into account from the start. Knottnerus, Heijmans and Rademakers [34] showed that this was not unique to the rheumatology context, but extends across people with chronic diseases in the Netherlands. While the intersection between crisis communication and health literacy should be further explored, investing in training and guidelines for health literate communication for organisations and health professionals will potentially be useful in general patient communication as well as in times of crisis.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies reported that people with lower health status [4] and people with rheumatic diseases [30] were aware of their vulnerability and therefore took precautions [30], this may not have been true for people with limited health literacy within those groups, who were found to perceive themselves less susceptible to COVID-19 infection [31,32] and were possibly less likely to take preventive measures [33]. A Dutch qualitative study on the COVID-19-related challenges of people with a chronic illness and limited health literacy highlighted the important role of one-on-one communication by trusted healthcare professionals, especially in providing information tailored to the health literacy needs and clinical profile of the individual [34]. Knowing that COVID-19 has exacerbated health inequalities [35][36][37] and health literacy plays a role in vaccine hesitancy [38,39], the need to consider health literacy in crisis communication is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate and valid measurements of health literacy are essential to identifying groups most at risk of low literacy to guide the design of interventions to improve health literacy and evaluate progress. It is especially important to assess health literacy in primary care practices where most of the patients have chronic conditions [13], and an increasing proportion of patients are managing and receiving information for more than one chronic condition [14,15]. To date, three measurement approaches of health literacy have been described: direct testing of individual abilities, and population-based proxy or self-report of abilities measures [16].…”
Section: Of 11mentioning
confidence: 99%